2016
DOI: 10.25088/complexsystems.25.2.127
|View full text |Cite
|
Sign up to set email alerts
|

On Complexity of Persian Orthography: L-Systems Approach

Abstract: To understand how the Persian language developed over time, we uncover the dynamics of complexity of Persian orthography. We represent Persian words by L-systems and calculate complexity measures of these generative systems. The complexity measures include degrees of nonconstructability, generative complexity, and morphological richness; the measures are augmented with time series analysis. The measures are used in a comparative analysis of four representative poets: Rudaki (858-940 AD), Rumi (1207-1273), Sohr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In the objective analysis, we showed the efficiency of the spike event detection method in comparison with the existing, in neuroscience, techniques of spike detection [37,47] and the expert opinion in locating spikes' arrival time. In the complexity analysis, we selected complexity measures used in previous studies [49,6,10,46] to quantify activity patterns that are spatio-temporally integrated and differentiated.…”
Section: Resultsmentioning
confidence: 99%
“…In the objective analysis, we showed the efficiency of the spike event detection method in comparison with the existing, in neuroscience, techniques of spike detection [37,47] and the expert opinion in locating spikes' arrival time. In the complexity analysis, we selected complexity measures used in previous studies [49,6,10,46] to quantify activity patterns that are spatio-temporally integrated and differentiated.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, they found that both elementary and advanced learners faced difficulty learning English orthography system while they betrayed almost no positive effect from their first language. Taghipour et al (2016) demonstrated that the Persian language contains much irregularity which is characterized by the complexity measures of L-systems which represent the words and that this irregularity has increased over the temporal evolution of the language. Furthermore, Baluch (2005) emphasized on how literacy acquisition by Persian beginner and skilled readers may be influenced by specific features of Persian orthography which affects cognitive processes involved in the reading of Persian.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we show the performance of the proposed postprocessing approach using morphological richness analysis [18] and fuzzy c-means (FCM) [8] based segmentation.…”
Section: Visual Analysismentioning
confidence: 99%